DETERMINING THE CURRENT CAPACITY OF TRANSMISSION LINES BASED ON AMBIENT CONDITIONS - Michal Špes; Ľubomír Beňa; Michal Kosterec; Michal Márton (Journal of Energy Technology, 2024)
After the incorrect prediction of generation from renewable sources, overloading of transmission lines occurred, resulting in the need for subsequent construction of new transmission lines and the maximum exploitation of existing power lines. One means of achieving this is to determine the permissible current load of power lines while respecting the surrounding climatic conditions. This article deals with determining the maximum current load of the power lines for changing various surrounding factors. The calculation is performed for conductor ACSR 350/59, which is used in the transmission system in Slovakia.